2019
DOI: 10.1126/science.aaw6102
|View full text |Cite
|
Sign up to set email alerts
|

Terminal coordination of diatomic boron monofluoride to iron

Abstract: Boron monofluoride (BF) is a diatomic molecule with 10 valence electrons, isoelectronic to carbon monoxide (CO). Unlike CO, which is a stable molecule at room temperature and readily serves as both a bridging and terminal ligand to transition metals, BF is unstable below 1800°C in the gas phase, and its coordination chemistry is substantially limited. Here, we report the isolation of the iron complex Fe(BF)(CO)2(CNArTripp2)2 [ArTripp2, 2,6-(2,4,6-(i-Pr)3C6H2]2C6H3; i-Pr, iso-propyl], featuring a terminal BF li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 63 publications
(62 reference statements)
2
54
0
Order By: Relevance
“…Monodentate isocyanide ligands play an important role in organometallic chemistry as alternatives to CO that can be further functionalized, [70][71] and one attractive option is to create polydentate chelating isocyanides. [72][73][74][75][76][77][78][79][80] In our initial communication, we reported that a m-terphenyl backbone is useful to obtain a diisocyanide ligand that binds Mo(0) in chelating fashion, giving access to a homoleptic complex (Scheme 1a, [Mo(L Me ) 3 ]) that is structurally and electronically similar to [Ru(bpy) 3 ] 2+ (bpy = 2,2'-bipyridine).…”
Section: Synthesis and Infrared Spectroscopymentioning
confidence: 99%
“…Monodentate isocyanide ligands play an important role in organometallic chemistry as alternatives to CO that can be further functionalized, [70][71] and one attractive option is to create polydentate chelating isocyanides. [72][73][74][75][76][77][78][79][80] In our initial communication, we reported that a m-terphenyl backbone is useful to obtain a diisocyanide ligand that binds Mo(0) in chelating fashion, giving access to a homoleptic complex (Scheme 1a, [Mo(L Me ) 3 ]) that is structurally and electronically similar to [Ru(bpy) 3 ] 2+ (bpy = 2,2'-bipyridine).…”
Section: Synthesis and Infrared Spectroscopymentioning
confidence: 99%
“…Moreover, these W 0 complexes with monodentate arylisocyanide ligands are very strong photoreductants, capable, for example, of reducing anthracene to its radical anion form. Many different kinds of metal complexes with isocyanide ligands have been explored over the past few decades [11][12][13][14][15], but metals with the d 6 or d 10 electron configurations are unique in their ability to show luminescence from a 3 MLCT excited state.…”
Section: Introductionmentioning
confidence: 99%
“…complexes with monodentate arylisocyanide ligands are very strong photoreductants, capable, for example, of reducing anthracene to its radical anion form. Many different kinds of metal complexes with isocyanide ligands have been explored over the past few decades [11][12][13][14][15], but metals with the d 6 or d 10 electron configurations are unique in their ability to show luminescence from a 3 MLCT excited state.Whilst structurally more flexible, multidentate isocyanide chelate ligands had been known for some time [16], we found that chelating diisocyanide ligands based on a m-terphenyl backbone permit the synthesis of homoleptic tris(diisocyanide) complexes of Cr 0 and Mo 0 that luminesce from 3 MLCT excited states (Figure 1) [17]. The molecular and the electronic structures of these compounds are reminiscent of Fe II and Ru II polypyridine complexes, which have been investigated extensively in the past.…”
mentioning
confidence: 99%
“…These encumbering ligands stabilize transition metal centers featuring high degrees of coordinative and electronic unsaturation. In addition, the kinetic protection afforded by m ‐terphenyl isocyanides has also allowed for the isolation of transition metal complexes featuring unusual ligands such as boron monofluoride (BF) and nitrous oxide (N 2 O) , . Such isocyanide ligands function as both strong σ‐donors and π‐acids , .…”
Section: Introductionmentioning
confidence: 99%
“…m ‐Terphenyl isocyanides have been shown to be useful ancillary ligands for the isolation of unusual and highly reactive transition metal complexes . These encumbering ligands stabilize transition metal centers featuring high degrees of coordinative and electronic unsaturation.…”
Section: Introductionmentioning
confidence: 99%